Protein and amino acid composition of different quinoa (chenopodium quinoa willd) cultivars grown under field conditions in Ethiopia, Kenya, Uganda, and Zambia - Lung'aho, Mercy G.; Fenta, A.B.; Wanderi, S.; Otim, A.; Mwaba, C.; Nyakundi, Fridah Nyabate; Abang, Mathew M. (African Journal of Food, Agriculture, Nutrition and Development, 2020)
Protein-energy malnutrition (PEM) remains a public health concern in most developing nations. In Africa, PEM can be attributed to monotonous diets based on cereals, roots, and tubers, with little or no protein of animal origin. Diversifying cropping systems to include protein dense pseudo-cereals such as Quinoa (Chenopodium quinoa Willd.) could help provide more protein in the diet of vulnerable populations. Quinoa is a crop with potential for biodiversification because it has a high nutritional value; however, it is underutilized in Africa, and information about the nutritional quality of the grain grown in contrasting environments is limited. Within the framework of FAO’s commemoration of 2013 as the ‘The International Year of the Quinoa’ (IYQ), a Technical Cooperation Programme (TCP) project was developed with some African countries to assess the capacity of quinoa to adapt to different agro-ecological regions and the nutritional quality of the resulting grain. For this study, we evaluated the protein content and amino acid profile of three genotypes of quinoa that had been grown under diverse altitudes, soil, and climate conditions in Ethiopia, Kenya, Uganda, and Zambia. The mean protein content (g/100g) of Kancolla, Titicaca and BBR varieties grown in Africa ranged from 14.33 ±0.20 to 17.61 ±0.55, 14.23 ±0.25 to 16.65 ±0.55, and 13.13 ±0.2 to 16.23 ±0.49, respectively. On the other hand, the protein content (g/100g) of Kancolla, Titicaca, and BBR seeds grown in Peru was 13.80 ±0.10, 17.43 ±0.31, and 17.07 ±0.11, respectively. The Kancolla variety [grown in Ethiopia and Kenya] had a significantly higher protein content than that obtained from Peru [P < 0.001]. Regarding the profile of essential amino acids, Quinoa is essentially richer in methionine than most cereals. Levels of methionine were lower in the seeds grown in Africa compared to those from Peru [P < 0.001]. In terms of environmental influences, the protein content was relatively higher in quinoa seeds grown in high-altitude areas, where soils have a low pH and high nitrogen content. We conclude that Quinoa can be introduced to Africa, especially to high altitudes and warm regions where the soil has a low pH and high nitrogen content. The crop would be ideal for diversifying local diets.